2010
DOI: 10.1007/s00422-010-0401-y
|View full text |Cite
|
Sign up to set email alerts
|

What do the basal ganglia do? A modeling perspective

Abstract: Basal ganglia (BG) constitute a network of seven deep brain nuclei involved in a variety of crucial brain functions including: action selection, action gating, reward based learning, motor preparation, timing, etc. In spite of the immense amount of data available today, researchers continue to wonder how a single deep brain circuit performs such a bewildering range of functions. Computational models of BG have focused on individual functions and fail to give an integrative picture of BG function. A major break… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
131
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(136 citation statements)
references
References 101 publications
3
131
0
2
Order By: Relevance
“…Fluctuations in incentive motivation were also found to correlate with activity in brain regions involved in attention and motor function, as well as with activity in the dopaminergic midbrain and its projection sites such as the ventral striatum (Knutson et al, 2001a;Knutson et al, 2005;Tobler et al, 2005). These findings, together with findings highlighting a crucial role for DA in activational aspects of behaviour Everitt, 1992, 2007), have led researchers to suggest that the impact of motivation on behaviour is mediated by DA (Chakravarthy et al, 2010;Salamone and Correa, 2012;Wise, 2004). Several studies have also shown that the same neural circuitry may also represent the expected value of stimuli presented to one hemifield, but largely restricted to the contralateral hemisphere (Gershman et al, 2009;Palminteri et al, 2009;Wunderlich et al, 2009), suggesting the possibility of unilaterally activating the brain's motivational system.…”
Section: Biased Computational Reinforcement Learning Relates To Spatimentioning
confidence: 93%
“…Fluctuations in incentive motivation were also found to correlate with activity in brain regions involved in attention and motor function, as well as with activity in the dopaminergic midbrain and its projection sites such as the ventral striatum (Knutson et al, 2001a;Knutson et al, 2005;Tobler et al, 2005). These findings, together with findings highlighting a crucial role for DA in activational aspects of behaviour Everitt, 1992, 2007), have led researchers to suggest that the impact of motivation on behaviour is mediated by DA (Chakravarthy et al, 2010;Salamone and Correa, 2012;Wise, 2004). Several studies have also shown that the same neural circuitry may also represent the expected value of stimuli presented to one hemifield, but largely restricted to the contralateral hemisphere (Gershman et al, 2009;Palminteri et al, 2009;Wunderlich et al, 2009), suggesting the possibility of unilaterally activating the brain's motivational system.…”
Section: Biased Computational Reinforcement Learning Relates To Spatimentioning
confidence: 93%
“…Several of the functions that are ascribed to the basal ganglia, together with the role of prediction error in each of these functions, can be captured through reinforcement learning models (Chakravarthy, Joseph, & Bapi, 2010).…”
Section: Modelmentioning
confidence: 99%
“…Studies on functional magnetic resonance imaging (fMRI) have recognized the anatomic sections, which are active during swallowing, including the chief sensory and motor cortex, additional motor area (SMA), cingulate cortex, insula, operculum, prefrontal and inferior frontal cortices, BG, thalamus, and cerebellum [43][44][45][46][47][48]. As mentioned earlier, automatic movements of swallowing are controlled by BG that establishes accurate timing and spacing in this process [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Recognized swallow-associated augmented blood in the putamen PET Hartnick et al [29] Rise in swallow-induced local activity in putamen, globus pallidus, and substantia nigra f-MRI Suzuki et al [30] The right putamen was introduced as a focal point for activation f-MRI Martin et al [31] Discovered BG activation through water oral combination f-MRI PET Hamdy et al [20] I ranian R ehabilitation Journal which are primary and secondary somato-sensory, primary motor cortex, and premotor areas [37,38]. In addition, BG has extensive connections with the thalamus and other sub-cortical structures [39,40].…”
Section: Imaging Technique Referencesmentioning
confidence: 99%